Reuse in the Big Data Era : 18th International Conference on Software and Systems Reuse, ICSR 2019, Cincinnati, OH, USA, June 26-28, 2019, Proceedings /: 18th International Conference on Software and Systems Reuse, ICSR 2019, Cincinnati, OH, USA, June 26-28, 2019, Proceedings. ([2019]) - Unknown
No abstract available